Epistemology of Interdisciplinary Research at Islamic Study on State Islamic Religious Higher Education in Indonesia - Rudhad Ilaina; Nur Ahid; Andika Eko Presetiyo (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2022)
Nowadays, Islamic studies research should not be limited to the use of the Nash text study paradigm, such as the classical Islamic scientific tradition. The monodisciplinary approach is no longer sufficient to answer the challenges of the times faced by Muslims in various worlds, for example, the problem of the Covid-19 pandemic that has hit since 2019. Islamic studies using an interdisciplinary, multidisciplinary, and transdisciplinary approach are expected to be the answer to the challenges of the modern and contemporary Islamic world today. This paper uses a qualitative descriptive method with a literature review related to interdisciplinary research in Islamic Studies by content analysis approach. In conclusion, first, there are some approaches applied to Islamic studies, namely normative theological, anthropological approaches, sociological approaches, philosophical approaches, historical approaches, cultural approaches, psychological approaches, and hermeneutic approaches. Secondly, in applying these interdisciplinary approaches to Islamic studies, problems can be solved using a number of approaches or points of view at once, for example using sociological, historical, and normative approaches simultaneously, or several other approaches. Third, the results of these interdisciplinary Islamic studies can develop, enrich and produce the intellectual treasures of Islamic studies at State Islamic Religious Higher Education in Indonesia (PTKIN)